Pembuatan Beras Analog Berbahan Tepung Sukun (Artocarpus communis) - Pirnando, Heri; Tamrin, Tamrin; Rahmawati, Winda; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2022)
Analog rice can be used as a diversification and substitution of rice, in order to overcome the shortage of rice production, breadfruit become the choice in making analog rice because of its very much growth in Indonesia. The purpose of this study was to determine the effect of tapioca flour concentration in making analog rice which is the main raw material for breadfruit flour. The process of making analog rice includes weighing the ingredients, mixing the ingredients, granulating the ingredients, and giving water. This research method is mixing breadfruit flour with tapioca flour with five levels, namely 0%, 5%, 10%, 15%, and 20% tapioca flour with the testing stage is analog rice steaming, rice drying, measurement of test parameters, data and test results parameters, then the parameters observed were (water absorption, grain diameter, water absorption, bulk density and proximate). The more tapioca flour additions, the analog rice water content increased ie the first treatment was 7.11% while the fifth treatment was 7.91%. The more tapioca flour is added, the less weight percentage with grain size <2 mm while the percentage weight with 4.7 mm grain size is getting higher. Then the addition of tapioca flour to water absorption decreased the first treatment by 102.69% and the fifth treatment was 88.01%.